The effect of sex on social cognition and functioning in schizophrenia - Marta Ferrer-Quintero; Michael F. Green; William P. Horan; David L. Penn; Robert S. Kern; Junghee Lee (npj Schizophrenia, 2021)
Abstract Social cognitive impairment is a core feature of schizophrenia and plays a critical role in poor community functioning in the disorder. However, our understanding of the relationship between key biological variables and social cognitive impairment in schizophrenia is limited. This study examined the effect of sex on the levels of social cognitive impairment and the relationship between social cognitive impairment and social functioning in schizophrenia. Two hundred forty-eight patients with schizophrenia (61 female) and 87 healthy controls (31 female) completed five objective measures and one subjective measure of social cognition. The objective measures included the Facial Affect Identification, Emotion in Biological Motion, Self-Referential Memory, MSCEIT Branch 4, and Empathic Accuracy tasks. The subjective measure was the Interpersonal Reactivity Index (IRI), which includes four subscales. Patients completed measures of social and non-social functional capacity and community functioning. For objective social cognitive tasks, we found a significant sex difference only on one measure, the MSCEIT Branch 4, which in both patient and control groups, females performed better than males. Regarding the IRI, females endorsed higher empathy-related items on one subscale. The moderating role of sex was found only for the association between objective social cognition and non-social functional capacity. The relationship was stronger in male patients than female patients. In this study, we found minimal evidence of a sex effect on social cognition in schizophrenia across subjective and objective measures. Sex does not appear to moderate the association between social cognition and functioning in schizophrenia.